Post-Quantum Cryptography - Buchmann, Johannes (Springer, 2017)
This book constitutes the refereed proceedings of the Second International Workshop on Post-Quantum Cryptography, PQCrypto 2008, held in Cincinnati, OH, USA, in October 2008.